Incidence of type 2 diabetes mellitus and hyperlipidemia in patients prescribed dasatinib or nilotinib as first- or second-line therapy for chronic myelogenous leukemia in the US. (1st February 2018) - Franklin, Meg; Burns, Leah; Perez, Samuel; Yerragolam, Deepak; Makenbaeva, Dinara
Abstract: Objective: Evaluate the incidence of type 2 diabetes mellitus (T2DM) and hyperlipidemia (HLD) in CML patients initiating therapy with dasatinib or nilotinib. Methods: Retrospective study using MarketScan claims from January 2006 to December 2014. The first analysis evaluated occurrence of T2DM, defined as ≥2 claims with a T2DM ICD-9 code or 1 diagnosis claim and an antidiabetic medication. The second analysis evaluated occurrence of HLD, defined as ≥2 claims with an HLD ICD-9 code, or 1 diagnosis claim and an anti-HLD medication. Incidence rates were computed as number of events divided by sum of person years (PY) at risk for all subjects. Multivariate Cox proportional hazards models estimated hazard ratios (HRs) for T2DM or HLD. Results: There were 2004 and 1280 patients who met the criteria for the T2DM analysis ( n  = 1272 dasatinib, n  = 732 nilotinib) and HLD analysis ( n  = 845 dasatinib, n  = 435 nilotinib). The incidence rate of T2DM was 40.4 per 1000 PY (95% CI: 27.60, 56.98) for nilotinib and 17.6 per 1000 PY (95% CI: 11.14, 26.38) for dasatinib. HR for occurrence of T2DM was 2.77 (95% CI: 1.58, 4.86), indicating that patients on nilotinib had a significantly higher adjusted risk for incident T2DM. The incidence rate of HLD was 74.6 per 1000 PY (95% CI: 50.70, 105.94) for nilotinib and 46.4 per 1000 PY (95% CI: 33.00, 63.45) for dasatinib. HR for occurrence of HLD was 1.75 (95% CI: 1.07, 2.87) indicating that patients on nilotinib had a significantly higher adjusted risk for incident HLD. Conclusions: Patients receiving nilotinib had significantly higher rates of incident T2DM or HLD than patients on dasatinib.